2017
DOI: 10.1155/2017/8390575
|View full text |Cite|
|
Sign up to set email alerts
|

Enamel Thickness before and after Orthodontic Treatment Analysed in Optical Coherence Tomography

Abstract: Despite the continuous development of materials and techniques of adhesive bonding, the basic procedure remains relatively constant. The technique is based on three components: etching substance, adhesive system, and composite material. The use of etchants during bonding orthodontic brackets carries the risk of damage to the enamel. Therefore, the article examines the effect of the manner of enamel etching on its thickness before and after orthodontic treatment. The study was carried out in vitro on a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…To date, only 2 recent publications have revealed significant agreement in the potential of OCT as a clinical tool to effectively measure the whole enamel layer thickness. 15,16 Some publications have acknowledged the risk of using ceramic brackets and Suliman et al widened the available knowledge on the topic by evaluating 2 types of these brackets, in which polycrystalline brackets were found to be more dangerous to the enamel structure. [17][18][19] A number of studies evaluating the loss of enamel thickness and surface damage following the removal of brackets have been published, in which the measuring tools were a planer surfometer and profilometer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 2 recent publications have revealed significant agreement in the potential of OCT as a clinical tool to effectively measure the whole enamel layer thickness. 15,16 Some publications have acknowledged the risk of using ceramic brackets and Suliman et al widened the available knowledge on the topic by evaluating 2 types of these brackets, in which polycrystalline brackets were found to be more dangerous to the enamel structure. [17][18][19] A number of studies evaluating the loss of enamel thickness and surface damage following the removal of brackets have been published, in which the measuring tools were a planer surfometer and profilometer.…”
Section: Discussionmentioning
confidence: 99%
“…Seeliger et al 41 and Koprowski et al 42 studied enamel thickness before and after orthodontic treatment using OCT and concluded that optical coherence tomography is an efficient aid in evaluating the surface and cross-sectional characteristics of enamel post-orthodontic treatment and it provides valuable information for deciding on the methodology and course of orthodontic treatment.…”
Section: Use Of Oct In Orthodonticsmentioning
confidence: 99%
“…Enamel, being a hard protector of the teeth can be chipped and cracked exposing the underlying dentinal tubules during different procedures in carrying out orthodontic treatment, which predisposes to DH. The surface texture of enamel is irreversibly affected [ 1 ], with a definite reduction in the thickness of enamel before and after orthodontic treatment [ 2 ]. There is qualitative as well as a quantitative loss of enamel reported from invitro studies related to the factors such as the initial prophylaxis [ 3 , 4 ], type of etchant used [ 5 ], duration of etching [ 1 ], adhesive characteristics such as filled and unfilled [ 3 , 5 ], self etching primer and enamel clean-up methods [ 6 ] light cured v/s self cure [ 7 ], type of adhesive retention [ 8 ] and type of bracket, metallic or ceramic [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%